Bacterial conversion of waste into polyhydroxybutyrate (PHB): A new approach of bio-circular economy for treating waste and energy generation. (September 2019) - Reddy, M. Venkateswar; Mawatari, Yasuteru; Onodera, Rui; Nakamura, Yuki; Yajima, Yuka; Chang, Young-Cheol
Abstract: In this study, several wastewaters were evaluated for polyhydroxybutyrate (PHB) production using the pure bacterial culture of Bacillus sp. CYR1, and co-cultures of Bacillus sp. CYR1- Cupriavidus sp. CY1. Mixed cultures were also used for wastewater treatment. Carbon removal in the wastewaters was evaluated using chemical oxygen demand (COD) and total organic carbon (TOC) analyzers. Additionally, PHB production was evaluated for incorporating lowest (0.1 g/l) and highest (107 g/l) COD-containing wastewaters by using pure bacterial culture. PHB granules present inside bacterial cells were observed using transmission electron microscopy. Extracted PHB evaluated for structure, physical properties and molecular weight determination. Highest PHB production was observed with wastewater collected from a cheese whey factory (151 mg/l), and sewage treatment plant (145 mg/l). The results obtained denoted that the waste could be used for the production of valuable materials using microbial fermentation technologies. Highlights: Pure culture and co-cultures were used for PHB production. PHB production was evaluated with lowest and highest COD containing wastewaters. PHB granules present inside bacterial cells were observed using TEM. Thermal and physical properties of the PHB were evaluated using analytical methods.